2017
DOI: 10.1016/j.rvsc.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mono- and co-infection by swine influenza A viruses and porcine respiratory coronavirus in porcine precision-cut lung slices

Abstract: Coronaviruses as well as influenza A viruses are widely spread in pig fattening and can cause high economical loss. Here we infected porcine precision-cut lung slices with porcine respiratory coronavirus and two Influenza A viruses to analyze if co-infection with these viruses may enhance disease outcome in swine. Ciliary activity of the epithelial cells in the bronchus of precision-cut lung slices was measured. Co-infection of PCLS reduced virulence of both virus species compared to mono-infection. Similar re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…SwIAV and PCV2 as primary infectious agents have been less studied. However, it can be observed that swIAV can interfere with other virus productions (PRRSV and PRCoV) [85,86] whereas PCV2 has some detrimental impact on the clinical outcome of secondary viral infections (PRRSV, swIAV, and PPV) [87][88][89] (see Additional file 1 and Figure 1A). Then, regarding the inflammation induced in coinfection conditions, various outcomes were observed depending which viruses were considered (Figure 2A).…”
Section: The Different Types Of Coinfections 321 Virus-virusmentioning
confidence: 99%
“…SwIAV and PCV2 as primary infectious agents have been less studied. However, it can be observed that swIAV can interfere with other virus productions (PRRSV and PRCoV) [85,86] whereas PCV2 has some detrimental impact on the clinical outcome of secondary viral infections (PRRSV, swIAV, and PPV) [87][88][89] (see Additional file 1 and Figure 1A). Then, regarding the inflammation induced in coinfection conditions, various outcomes were observed depending which viruses were considered (Figure 2A).…”
Section: The Different Types Of Coinfections 321 Virus-virusmentioning
confidence: 99%
“…Focusing on the IFN-ω members and their antiviral and inflammatory regulation, we characterized family-wide porcine innate immune IFNs for their functional spectrum and therapeutic potential (9, 10, 13, 14), which was profiled against two RNA viruses: porcine reproductive and respiratory syndrome virus (PRRSV), and influenza A virus. Both viruses have a high impact on the swine industry and influenza A virus in swine, also threatens public health (13, 16). Here, we show that vertebrate IFN-ω subtype has evolved several novel features, which include: (1) being a signature multi-gene subtype expanding particularly in bats and ungulates (7, 9, 17, 18), (2) emerging isoforms that have much higher antiviral potency than typical IFN-α (14, 18, 19), (3) highly cross-species antiviral (but little anti-proliferative) activity exerted in cells of humans and other mammalian species (20), and (4) other potential novel molecular and functional properties (3, 4, 18, 20).…”
Section: Introductionmentioning
confidence: 99%
“…Primary porcine tracheal epithelial cells (PTECs) and primary porcine bronchial epithelial cells (PBECs) were harvested from the 5-month-old pigs’ trachea and bronchial, respectively, as previously described [ 19 , 20 ]. Briefly, PTECs and PBECs firstly maintained in bronchial epithelial cell growth medium (Lonza, Basel, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were incubated in a humidified atmosphere containing 5% CO 2 at 37 °C and passaged every 2 to 3 days. PRCoV Bel85 was obtained from Luis Enjuanes [ 20 ]. The virus stock was propagated on ST cells in EMEM.…”
Section: Methodsmentioning
confidence: 99%